Microcontroller Programming. The Microchip PIC - Sanchez J. Julio (New York, Taylor & Francis, 2007)
From cell phones and television remote controls to automobile engines and spacecraft, microcontrollers are everywhere. Programming these prolific devices is a much more involved and integrated task than it is for general-purpose microprocessors; microcontroller programmers must be fluent in application development, systems programming, and I/O operation as well as memory management and system timing. Using the popular and pervasive mid-range 8-bit Microchip PIC® as an archetype, Microcontroller Programming offers a self-contained presentation of the multidisciplinary tools needed to design and implement modern embedded systems and microcontrollers. The authors begin with basic electronics, number systems, and data concepts followed by digital logic, arithmetic, conversions, circuits, and circuit components to build a firm background in the computer science and electronics fundamentals involved in programming microcontrollers. For the remainder of the book, they focus on PIC architecture and programming tools and work systematically through programming various functions, modules, and devices. Helpful appendices supply the full mid-range PIC instruction set as well as additional programming solutions, a guide to resistor color codes, and a concise method for building custom circuit boards.